The reinvention laborataories: strategic change by indirection - Thompson, James R. (2000)
The reinvention laboratories created as part of the National Performance Review represent a novel approach to strategic change in the federal government. In assigning an important role to middle management in the design and implementation of new work technologies, the lab program contrasts with more conventional approaches to change in which top management is dominant. This study examines the viability of the generative model that the lab program represents as a means of inducing agencies to employ postbureaucratic organizing principles. A conclusion is that although a variety of factors will affect the degree of success achieved, the model holds promise as a means of achieving strategic change in public organizations. - Reproduced
Keywords: Organizational change